2018
DOI: 10.1587/transinf.2018edp7175
|View full text |Cite
|
Sign up to set email alerts
|

Salient Feature Selection for CNN-Based Visual Place Recognition

Abstract: Recent researches on mobile robots show that convolutional neural network (CNN) has achieved impressive performance in visual place recognition especially for large-scale dynamic environment. However, CNN leads to the large space of image representation that cannot meet the real-time demand for robot navigation. Aiming at this problem, we evaluate the feature effectiveness of feature maps obtained from the layer of CNN by variance and propose a novel method that reserve salient feature maps and make adaptive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Experimental results showed that SSM-VPR achieved an impressive recognition effect. However, in terms of image representation space and matching efficiency, SSM-VPR was inferior to the method in [30]. Besides, the inability to distinguish the saliency of landmark areas was also a disadvantage of these methods.…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…Experimental results showed that SSM-VPR achieved an impressive recognition effect. However, in terms of image representation space and matching efficiency, SSM-VPR was inferior to the method in [30]. Besides, the inability to distinguish the saliency of landmark areas was also a disadvantage of these methods.…”
Section: Related Workmentioning
confidence: 98%
“…Based on pre-trained CNN models, they fully analyzed the meaning of the original CNN features and made full use of the activations for landmark selection. Chen et al [30] evaluated the feature effectiveness of feature maps obtained from the layer of CNN by variance and proposed a novel method that reserved salient feature maps to achieve fast image matching. This method greatly reduced the space of image representation to half of the original CNN features with a tolerable loss in accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Among these methods, feature extraction on the entire image for place recognition introduces redundant information and reduces efficiency. Considering that CNN leads to the large space of image representation, Chen et al 30 proposed a new method of reserving salient feature maps and make adaptive binarization on it, and the experimental results proved the effectiveness. Since the highly representative landmark features are robust to appearance changes, Xin et al 31 proposed an effective method based on CNNs and content-based multiscale landmarks to complete the task of place recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, CNNs have high potential for use in spatiotemporal fusion technology for remote sensing images. Most previous studies have discussed feature extraction from CNNs [8,9]. However, relatively few studies have discussed CNN algorithms for the spatiotemporal fusion of satellite images.…”
Section: Introduction 1motivationmentioning
confidence: 99%